2022
DOI: 10.1038/s41598-022-06264-x
|View full text |Cite
|
Sign up to set email alerts
|

A promising deep learning-assistive algorithm for histopathological screening of colorectal cancer

Abstract: Colorectal cancer is one of the most common cancers worldwide, accounting for an annual estimated 1.8 million incident cases. With the increasing number of colonoscopies being performed, colorectal biopsies make up a large proportion of any histopathology laboratory workload. We trained and validated a unique artificial intelligence (AI) deep learning model as an assistive tool to screen for colonic malignancies in colorectal specimens, in order to improve cancer detection and classification; enabling busy pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 42 publications
(38 reference statements)
0
43
0
Order By: Relevance
“…To deploy in practical histopathological diagnostic workflow system for screening colon biopsies, a recent study (20) modeled the classification of epithelial tumors (adenocarcinoma and adenoma) with a large development cohort (n=4 036) and small validation cohorts (n=500, and TCGA-COAD: n=547). A more recent study (21) used gland segmentation and classification to model categorization of ‘low risk’ (benign, inflammation) and ‘high risk’ (dysplasia, malignancy) slides with a small cohort (n=294). However, these models do not cater for early diagnosis and lack high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…To deploy in practical histopathological diagnostic workflow system for screening colon biopsies, a recent study (20) modeled the classification of epithelial tumors (adenocarcinoma and adenoma) with a large development cohort (n=4 036) and small validation cohorts (n=500, and TCGA-COAD: n=547). A more recent study (21) used gland segmentation and classification to model categorization of ‘low risk’ (benign, inflammation) and ‘high risk’ (dysplasia, malignancy) slides with a small cohort (n=294). However, these models do not cater for early diagnosis and lack high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…It extracts features, makes detections through these features, and quantifies the degree of fit at each detection using a value of possibility ranging from the worst of 0 to the optimum of 100. Evidence has shown that Faster-RCNN is especially good at detecting objects at multiple scales and aspect ratios, such as abnormal cervical cells in cytology images and cancer regions in colorectal biopsies ( 17 , 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…The sliding-window technique was used to break these down into smaller images. Other studies used various images, such as endoscopic and whole slide images (WSI) for the detection of colon cancer [ 46 , 47 ]. Another study used a larger image size (768 × 768 pixels) to preserve tissue architecture information and reduce computational cost, as opposed to a smaller patch size (384 × 384 pixels), which produced the same result but had a higher computational cost [ 48 ].…”
Section: Imaging Modalitiesmentioning
confidence: 99%